Broken hearts & dirty windows [compact disc] : songs of John Prine. Vol. 2 - Prine, John (Oh Boy Records, 2022)
The follow-up to the 2010 John Prine tribute album sees more of music's biggest and brightest pay homage to the late singer-songwriter. Included are tracks from Brandi Carlile and Sturgill Simpson.